2004
DOI: 10.2486/indhealth.42.415
|View full text |Cite
|
Sign up to set email alerts
|

Lead Levels in Urine of Never-Smoking Adult Women in Non-Polluted Areas in Japan, with References to Cadmium Levels in Urine

Abstract: The present study was initiated to assess current level of general population exposure to lead (Pb) in terms of Pb in urine (Pb-U). For this purpose, spot urine samples were collected from 2,332 never-smoking adult women in 10 areas all-over Japan, and were subjected to analysis for Pb-U by graphite furnace atomic absorption (GFAA). Data on cadmium in urine (Cd-U) as measured by GFAA were cited from a previous publication 1) . The grand geometric means (GM) for Pb-U as observed, as corrected for creatinine (cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 33 publications
(43 reference statements)
2
3
1
Order By: Relevance
“…The mean ULL for both the pregnant women and the control group were consistent with reports from other Nigerian investigators (Ademuyiwa et al 2002;Ogunfowokan et al 2002) but high in comparison to the results reported outside Nigeria (0.77 to 5.4 μg/dL) by Fukui et al (2004), confirming increased environmental Pb in Lagos at the time of study. The results from this study on the correlation between ULL and BLL ran contrary to some literature reports that gave high and significant relationships.…”
Section: Relationship Of Blood and Urine Lead Levels To Age Of Responsupporting
confidence: 94%
“…The mean ULL for both the pregnant women and the control group were consistent with reports from other Nigerian investigators (Ademuyiwa et al 2002;Ogunfowokan et al 2002) but high in comparison to the results reported outside Nigeria (0.77 to 5.4 μg/dL) by Fukui et al (2004), confirming increased environmental Pb in Lagos at the time of study. The results from this study on the correlation between ULL and BLL ran contrary to some literature reports that gave high and significant relationships.…”
Section: Relationship Of Blood and Urine Lead Levels To Age Of Responsupporting
confidence: 94%
“…The found U-Pb concentrations indicate higher exposure in the study population (median, 2.8 and 3.8 µg/L for maternal and concurrent levels, respectively) than in U.S. women and children (median, ~ 0.7 µg/L), and more similar to that observed in Japanese women (median, 1.2 µg/L) (CDC 2010; Fukui et al 2004). Still, we found no significant association of U-Pb with children’s IQ or behavior.…”
Section: Discussionsupporting
confidence: 62%
“…Pb-B was measured by graphite furnace atomic absorption spectrometry as previously described; the limit of detection in practice was 5 µg Pb/100 ml blood 12,15) . ALA-U was measured by two methods, i.e., by colorimetry after Tomokuni and Ichiba 3) , and by HPLC after Okayama et al 5) .…”
Section: Methods Of Determination Of Lead In Blood and δ-Aminolevulinmentioning
confidence: 99%